A Case Study of the Crisis Communications Used in the 2009 Salmonella Outbreak in Peanut Products - Erica Irlbeck; Jessica Fry Jennings; Courtney Meyers; Courtney Gibson; Todd Chambers (Journal of Applied Communications, 2013)
The 2009 Salmonella outbreak in peanut products caused by contaminated peanut butter created a period of negative publicity for the peanut industry in the United States. It was one of many large food outbreaks the United States has seen in the past few years. Although one company was the cause of the outbreak, the peanut industry worked together to maintain its reputation. Crisis communications plans were put into effect, and crisis management teams worked together throughout. The purpose of this study was to examine the crisis communications efforts taken by peanut industry public relations practitioners during the 2009 Salmonella outbreak and determine which efforts had a successful outcome and which were ineffective. A case study methodology was employed whereby interviews with public relations practitioners that were working in the peanut industry during the crisis were conducted to address the research objectives. The findings indicate that a crisis communications plan is imperative for any organization, with the understanding that every crisis is unique and plans should be adapted accordingly. Plans should include, at the minimum, a crisis management team, a list of audiences that should be contacted, and key messages. In addition, media training should be conducted for potential spokespeople and relationships should be developed with members of the media before a crisis occurs. Investigation of the data and literature allowed the researchers to create a pre-crisis, crisis, and post-crisis model for agricultural communications.
Keywords: risk & amp; crisis communication; Salmonella; foodborne illness; public relations; peanuts